"Do Newspapers Add to Citizen Feelings of Community Closeness?"; Time for a New Look at Training for Rural-Based Development Projects - Debrah Jefferson; Jim King (Journal of Applied Communications, 1986)
Reviews of "Do Newspapers Add to Citizen Feelings of Community Closeness?" by C.N. Olien, G.A. Donohue, and P.J. Tichenor; Time for a New Look at Training for Rural-Based Development Projects, by John L. Woods.